Advances in Biocompatible and Biodegradable Polymers Volume II - Ferri, José Miguel; Fombuena Borràs, Vicent; Aldás Carrasco, Miguel Fernando (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Among the strategies for reducing the negative effects on the environment effected by the uncontrolled consumption and low potential for the recovery of conventional plastics, the synthesis of new biodegradable and recyclable plastics represents one of the most promising methods for minimizing the negative effects of conventional non-biodegradable plastics. The spectrum of existing biodegradable materials is still very narrow; thus, to achieve greater applicability, research is being carried out on biodegradable polymer mixtures, the synthesis of new polymers, and the incorporation of new stabilizers for thermal degradation, alongside the use of other additives such as antibacterials or new and more sustainable plasticizers. Some studies analyze direct applications, such as shape memory foams, new cartilage implants, drug release, etc.The reader can find several studies on the degradation of biodegradable polymers under composting conditions; however, novel bacteria that degrade polymers considered non-biodegradable in other, unusual conditions (such as conditions of high salinity) are also presented.